The politics of liberty in England and revolutionary America - Ward, Lee, 1970- (Cambridge University Press, 2004)
"This study locates the philosophical origins of the Anglo-American political and constitutional tradition in the philosophical, theological, and political controversies in seventeenth-century England. By examining the quarrel between the proponents of the doctrine of natural liberty and the champions of divine right theory, this study identifies the source of modern liberal, republican, and conservative ideas about natural rights and government in the seminal works of the Exclusion Whigs Locke, Sidney, and Tyrrell and their philosophical forebears Hobbes, Grotius, Spinoza, and Pufendorf. This study illuminates how these first Whigs and their diverse eighteenth-century intellectual heirs such as Bolingbroke, Montesquieu, Hume, Blackstone, Otis Jefferson, Burke, and Paine contributed to the formation of Anglo-American political and constitutional theory in the crucial period from the Glorious Revolution to the American Revolution and the creation of a distinctly American understanding of rights and government in the first estate constitutions."--Jacket